Perancangan Website Sekolah pada SDN 103 Kabupaten Sinjai sebagai Salah Satu Sarana Pembelajaran Online dan Penyajian Informasi - Nahlah, Nahlah; Amiruddin, Amiruddin; Amansyah, Farida (INTEK: Jurnal Penelitian, 2017)
The existence of school's website is a necessity that can not be avoided anymore. School's website is very useful as one of online learning and information presenting medium and also as a prerequisite for some inter-schools competition. Without the school's website, a school can not be a winner in a particular competition, like "Fund Management of School Operation Assistance". This situation has been experienced by the State Elementary School 103 Sinjai which failed to get the championdue to unavailability of the school website. This research aims to design a school website for the State Elementary School 103 Sinjai. The website that will be created uses PHP and MySQL-based CMS. Content and features of the website is created as the result of interviews with school's parties. The collecting of data was done by observation, documentation, and literature study. The softwares that used were Xampp, Dreamweaver Macromedia, one of isntallation package of PHP, Apache web server, and MySQL, as well as Research and Development's CMS. After installation of the softwares and Research and Development's CMs was completed, it was followed by adjustment of website content by logging in to the admin page. The created website has domain link as follows : http://sdn103sinjai.sch.id which has been published since the beginning of May 2016 and has been used by school parties in providing information about the various (all sort of) school activities.